El discurso referido en la prensa durante la primera ola de la pandemia por COVID-19: análisis de las voces de los representantes del Gobierno español (Altre Modernità, 2022)
The voice of the President of the Government, Pedro Sánchez, and the voices of senior officials and experts (Salvador Illa and Fernando Simón), chosen by the Government, were the protagonists in the press and they had an enormous media impact during pandemic COVID-19.In the framework of the appraisal theory of Martin and White and of the communication of press, we consider that the use of reported speech is one of the keys to observe the presence of the actors in the written press. Moreover, for Charaudeau it is a tool to orient a particular interpretation of the facts, and to convey a certain image of a public character.In this paper, we analyse with a quantitative and qualitative approach the way in which journalists construct the image of government representatives through the use reporting verbs to introduce reported speech (Reyes 16-22) and the attitudes and emotions these verbs denote (Escribano, Voces 11). The corpus is constituted by news from the national newspapers El País, ABC, El Mundo published from March to June 2020, that is, during the proclamation of the first State of Alarm and the first phases of the de-escalation.
Keywords: verba dicendi; pandemia; teoría de la valoración; discurso periodístico; discurso reproducido